2007
DOI: 10.1099/vir.0.82421-0
|View full text |Cite
|
Sign up to set email alerts
|

Bovine spongiform encephalopathy: the effect of oral exposure dose on attack rate and incubation period in cattle

Abstract: The dose-response of cattle exposed to the bovine spongiform encephalopathy (BSE) agent is an important component of modelling exposure risks for animals and humans and thereby, the modulation of surveillance and control strategies for BSE. In two experiments calves were dosed orally with a range of amounts of a pool of brainstems from BSE-affected cattle. Infectivity in the pool was determined by end-point titration in mice. Recipient cattle were monitored for clinical disease and, from the incidence of patho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
124
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(136 citation statements)
references
References 42 publications
6
124
0
2
Order By: Relevance
“…All the data related to BSE pathogenesis in sheep and cattle (distribution in tissues and incubation period) were produced using this experimental approach (Bellworthy et al, 2005a, b;Foster et al, 1996Foster et al, , 2001a. In cattle, the oral challenge experiments performed with low doses (1 g or below) reproduced the main features observed in field cattle BSE (Wells et al, 2007), which supports the fact that oral inoculation is, in that context, a relevant model.…”
Section: Impact Of Oral Challenge On Tse Pathogenesismentioning
confidence: 66%
“…All the data related to BSE pathogenesis in sheep and cattle (distribution in tissues and incubation period) were produced using this experimental approach (Bellworthy et al, 2005a, b;Foster et al, 1996Foster et al, , 2001a. In cattle, the oral challenge experiments performed with low doses (1 g or below) reproduced the main features observed in field cattle BSE (Wells et al, 2007), which supports the fact that oral inoculation is, in that context, a relevant model.…”
Section: Impact Of Oral Challenge On Tse Pathogenesismentioning
confidence: 66%
“…All the data related to BSE pathogenesis in sheep and cattle (distribution in tissues and incubation period) were produced using this experimental approach (Bellworthy et al, 2005a;Bellworthy et al, 2005b;Foster et al, 1996;Foster et al, 2001). In cattle the oral challenge experiments performed with low doses (1g or below) reproduced the main phenotypic features observed in field cattle BSE (Wells et al, 2007), which support the relevance of the oral inoculation model in this context. However, it is accepted that oral challenge can reduce the incubation period and accelerates the dissemination of the agent into the organs (Ryder et al, 2009;Tabouret et al, 2010).…”
Section: Natural Tse and Experimental Challengesmentioning
confidence: 80%
“…Crosscontamination between feed intended for pigs or poultry and cattle feed could have occurred at the feedstuff factory, if feed lines for cattle and feed for monogastric species were not distinct, during the transport of feed or on the farm, especially in mixed farms with both cattle and pigs or poultry. The potential for cross-contamination is heightened by the potential for low-dose exposure causing infection; in an oral exposure study it was shown that cattle could become infected by as little as 1 mg of brain homogenate [63]. A statistically significant relationship between the pig density in a region and BAB cases has also been found in subsequent studies on both the GB data [58] and for other countries including Northern Ireland, France, Switzerland, and Spain [1,3,26,30,55], supporting this initial hypothesis of cross-contamination of cattle feed with feed intended for pigs, and possibly poultry; a spatial study on feed factories confirmed recently the use of MBM in monogastric feed as a risk factor for BSE [51].…”
Section: Routes Of Infectionmentioning
confidence: 99%